Investigation Of Plasma Stability Of The Prototype Plasma Lens For Positron Matching - Hamann Niclas; Jones Harry; Loisch Gregor; Formela Manuel; Ludwig Kai; Osterhoff Jens; Moortgat-Pick Gudrid (EPJ Web of Conferences)
The quest for novel technologies in the ever-evolving landscape of scientific exploration has led to the investigation of plasma lensing as a potential solution for optical matching devices for all kinds of positron sources. This research becomes increasingly significant as the need for higher event rate demands innovative concepts to increase positron yield and therefore luminosity. A prototype plasma lens has been developed and tested for the first time. Instabilities were observed during the first test trials. This paper presents the results of high-temporal resolution imaging to analyze the discharge instabilities. Furthermore, the results show splitting and bending discharge instabilities and heavy copper coating. Overcoming these challenges is pivotal for a future application of plasma lenses as an integral part of high-performance positron sources.